Answer:
two real, unequal roots
Step-by-step explanation:
y is definied as y = 3x - 1. Substitute 3x - 1 for y in xy = 9, obtaining:
x(3x - 1) = 9. Then:
3x^2 - x - 9 = 0. In this quadratic, the coefficients are a = 3, b = -1 and c = -9.
Calculating the discriminant b^2 - 4ac, we get (-1)^2 - 4(3)(-9), or 1 + 108, or 109. Because the discriminant is positive, we have two real, unequal roots.
15 - 5
14 - 5
13 - 5
12 - 5
11 - 5
10 - 5
9 - 5
8 - 5
7 - 5
6 - 5
5 - 5
I’m not sure if this was the answer you were looking for but I hoped it helped
Answer:
Step-by-step explanation:
-intercept(s): (
0
,
8
)
y=8
Answer:
I think its 19.1
Step-by-step explanation:
14 + 5.1
Maybe try
Answer:
y^3/4x
Step-by-step explanation:
Given that the expression 6x^2/5y multiplied by some unknown gives answer as 3xy^2/10
We know that if ab = c, the b = c/a
Using the same principle, we have
unknown value = 3xy^2/10 divided by 6x^2/y
Use the fact that a/b divided by c/d = ad/bc
We get unknown = 5y(3xy^2)/6x^2 (10)
=15xy^3/60x^2
Simplify the constant part 15/60 as 1/4
xy^3 /x^2y
X term becomes x/x^2 = 1/x
so multiplying term =y^3/4x